2023 Cattlemen’s Day Full Report - Liz Boyle (Kansas Agricultural Experiment Station Research Reports, 2023)
This report includes research conducted in 2022 on beef cattle management, reproduction, nutrition, and meat science conducted at Kansas State University.
Keywords: beef cattle management; reproduction; nutrition; meat science; prescribed burning; grazing; consumer preference